Characteristics and visual outcomes of patients hospitalized for ocular trauma in central China:2006-2011 - Ying Qi; Feng-Yan Zhang; Guang-Hua Peng; Yu Zhu; Feng-Yan Zhang; Wen-Zhan Wang; Jing Ma; Shi-Jie Ren (International Journal of Ophthalmology, 2015)
AIM: To complete the data of ocular trauma in central China, as a well-known tertiary referral center for ocular trauma, we documented the epidemiological characteristics and visual outcomes of patients hospitalized for ocular trauma in this region. METHODS: A retrospective study of patients hospitalized for ocular trauma in central China from 2006 to 2011 was performed. RESULTS: This study included 5964 eyes of 5799 patients. The average age was 35.5±21.8y with a male-to-female ratio of 2.8:1. The most common age was 45-59y age group. Most patients were farmers and workers (51.9%). The most common injuries were firework related (24.5%), road traffic related (24.2%), and work related (15.0%). Among the most common causative agents were firecrackers (24.5%), followed by metal/knife/scissors (21.4%). Most injuries occurred in January (14.2%), February (27.0%), and August (10.0%). There were 8.5% patients with ocular injuries combined with other injuries. The incidence of open ocular injuries (4585 eyes, 76.9%) was higher than closed ocular injuries (939 eyes, 15.7%). The incidences of chemical and thermal ocular injuries were 1.2% and 0.6%. Ocular trauma score (OTS) predicted final visual acuity at non light perception (NLP), 20/200-20/50 and 20/40 with a sensitivity of 100%, and light perception (LP)/hand motion (HM) and 1/200-19/200 with a specificity of 100%. CONCLUSIONS: This study provides recent epidemiological data of patients hospitalized for ocular trauma in central China. Some factors influencing the visual outcome include time interval between injury and visit to the clinic, wound location, open or closed globe injury, initial visual acuity, and OTS.